Experiences of bereavement and coping strategies among people who have lost their significant others to suicide. - Chikwande, Mutsawashe Jill (Midlands State University, 2019)
Suicide is one of the leading cause of death around the world. All age groups are targets of suicide. Major causes of suicide are depression, mental illness and even different life constraints. Pesticides, guns, poison and hanging are some of the other risk factors to suicide. The study reviewed that even though research has been done on suicide a blind eye has been paid to the experiences of people bereaved by suicide hence the purpose of this study. The qualitative approach was used in this study and the Interpretive Phenomenological Analysis was used to analyse data. Snowballing and Purposive sampling were used as sampling techniques to obtain data. Interviews were used as a method of data collection. Data was collected from ten participants who were bereaved by suicide directly and indirectly. A few expenses were made while conducting the study as participants were within the author’s reach. However, it was difficult to get many participants for the study. The study outlined that people bereaved by suicide suffer emotionally (guilt, blame, fear, etc.), behaviourally (lack of concentration, physical reactions, crying etc.) and socially (stigma, family disintegration, etc.) in their lives. However, they try by all means to survive through coping strategies like counselling, spirituality and having available social systems in the form of family or friends to enhance the bereaved’s psychological wellbeing. The study also identified recommendations that can be done to help people bereaved by suicide and how the bereaved can also cope with their lives fully.